Correlation between demographic and environmental factors and dental caries prevalence in a remote Indonesian coastal community: a cross-sectional study - Masyhudi, Masyhudi; Candra, Krishna Purnawan; Handayani, Esti; Ahmad, Islamudin; Bujang, Kopli (Universitas Padjadjaran, 2026)
Introduction: Dental caries is a significant global health concern. Factors such as socioeconomic status, diet, oral hygiene, and access to dental care influence its prevalence. Limited information exists on dental health in remote sea-floating villages. This study aimed to analyze the correlation between demographic and environmental factors and dental caries prevalence in a sea-floating community. Methods: This cross-sectional study was conducted in Malahing Village, a sea-floating village located adjacent to the Makassar Strait, 4 km east of Bontang city. Seventy-two respondents aged 5–59 years were examined for the DMFT index, while intrinsic factors (demographic and dental health behaviors) and extrinsic factors (environmental and dental health services) were collected via questionnaires. Data were analyzed using descriptive univariate analysis to determine variable characteristics and Spearman’s correlation analysis. Results: Dental caries prevalence was 98.61%, with a DMFT index of 10.01. Age (r=0.564, p=0.001), education (r=0.370, p=0.002), and occupation (r=0.273, p=0.020) showed strong, moderate, and weak positive correlations, respectively. Rainwater exposure (r=-0.353, p=0.003) showed a moderate negative correlation. Sex, dental health behaviors, water source, and dental visits were not significantly correlated with caries prevalence. Adults showed highest prevalence (66.67%) but low DMFT index (1.00). Government employees had high DMFT scores (4.61). Twice-daily brushing was uncommon (66.67%) among individuals with high DMFT scores (6.15). Patients who never visited a dentist (44.44%) showed high DMFT scores (8.33). Conclusions: In this underserved coastal community, demographic disadvantages and environmental exposures, particularly water sources, combined with limited dental care contribute to an elevated caries burden compared to the national and international levels. Despite complex associations with environmental factors, rainwater exposure showed negative correlation with caries prevalence, highlighting measurement challenges. The high proportion of patients never visited a dentist, low oral health awareness, and nonstandard water management highlight critical service gaps.